The Effect of Polyphenols on Working and Episodic Memory in Non-pathological and Pathological Aging: A Systematic Review and Meta-Analysis - de Vries, Karin; Medawar, Evelyn; Korosi, Aniko; Witte, A. Veronica (Frontiers in Nutrition, 2022)
Life expectancy steadily increases, and so do age-associated diseases, leading to a growing population suffering from cognitive decline and dementia. Impairments in working memory (WM) and episodic memory (EM) are associated with an increased risk of developing dementia. While there are no effective pharmacological therapies to preserve or enhance cognition and to slow down the progression from mild memory complaints to dementia so far, plant-based nutrients including polyphenols have been suggested to exert beneficial effects on brain aging. This review studies whether supplementary polyphenols are effective in maintaining or enhancing memory in (pathological) aging, and whether there are polyphenol efficiency differences between WM and EM. A systematic literature search was conducted and 68 out of 294 randomized clinical trials with 20 participants or more per group, aged 40 years or older were included. These covered a daily intake of 35-1600 mg polyphenols, e.g. flavonols, flavonoids, isoflovones, anthocyanins, and/or stilbenes, over the course of 2 weeks to 6.5 years duration. In total, around half of the studies reported a significantly improved performance after polyphenol administration compared to control, while 3 studies reported a worsening of performance, and the remainder did not observe any effects. According to pooled WM and EM meta-analysis of all memory outcomes reported in 49 studies, overall effect size for WM and EM indicated a significant small positive effect on EM and WM with similar estimates (b ~ 0.24, p < 0.001), with large study heterogeneity and significant Funnel asymmetry suggesting a positivity bias. These results remained similar when excluding studies reporting extremely large positive effects from the meta-analyses. While ginkgo biloba and isoflavones did not show benefits in subgroup meta-analyses, some effects emerged for extracts containing anthocyanins, other flavonoids and resveratrol, again potentially resulting from publication bias. This systematic review and meta-analysis indicate that short- to moderate-term polyphenol interventions might improve WM and EM in aging, however, publication bias seems likely, rendering definite conclusions difficult. Future, longer studies with larger samples and sensitive monitoring of cardiovascular and metabolic pathologies are needed to better understand the impact of age, (beginning) pathologies, sex/gender and long-term use on polyphenol action.